Fundamental challenges encountered by international graduate students: Action research to enhance the well-being of Turkish scholars abroad - Cobanoglu, Ayse; Cavdar, Duygu; Tutar, Peri; Avci, Dilek (Journal of International Students, 2026)
Adopting a mixed-methods approach within the participatory action research framework, this study aims to identify the challenges faced by Turkish graduate students studying abroad under state scholarships. The interviews were conducted with six former scholars and four experts from the Turkish Ministry of Education to ensure that the participants' voices directly informed the research process. Insights from these interviews guided the development of an online survey. The results highlighted psychosocial stressors, communication issues, and gaps in institutional support. Action items were disseminated to policymakers to inform practice changes. The findings led to policy recommendations, with the Ministry subsequently establishing a "Psychological Counseling and Guidance Unit" to provide online counseling to students abroad.